2016
DOI: 10.5966/sctm.2015-0365
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Excision of Heterotopic Ossification Leads to Re-Emergence of Mesenchymal Stem Cell Populations Responsible for Recurrence

Abstract: Trauma‐induced heterotopic ossification (HO) occurs after severe musculoskeletal injuries and burns, and presents a significant barrier to patient rehabilitation. Interestingly, the incidence of HO significantly increases with repeated operations and after resection of previous HO. Treatment of established heterotopic ossification is challenging because surgical excision is often incomplete, with evidence of persistent heterotopic bone. As a result, patients may continue to report the signs or symptoms of HO, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
40
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(40 citation statements)
references
References 28 publications
0
40
0
Order By: Relevance
“…NHOs can relapse, even 15 years after surgery (F. Genet, unpublished observations) (53), and our results indicate that NHO-MDSCs with osteogenic potential are still present in muscles after NHO resection. This hypothesis is strengthened by the recent study by Agarwal et al (54), showing that PDGFRα + MSCs are responsible for HO recurrence in a burn/tenotomy mouse model. Thus, when reactivated under specific conditions, residual NHO-MDSCs may participate in NHO recurrence.…”
Section: Discussionmentioning
confidence: 87%
“…NHOs can relapse, even 15 years after surgery (F. Genet, unpublished observations) (53), and our results indicate that NHO-MDSCs with osteogenic potential are still present in muscles after NHO resection. This hypothesis is strengthened by the recent study by Agarwal et al (54), showing that PDGFRα + MSCs are responsible for HO recurrence in a burn/tenotomy mouse model. Thus, when reactivated under specific conditions, residual NHO-MDSCs may participate in NHO recurrence.…”
Section: Discussionmentioning
confidence: 87%
“…In the current context, however, it is important to note that PDGFRα+ cells represented a small subfraction of both Mx1+ and Scx+ lineages[38]. In fact, one underlying commonality among most lineage-tracing studies that have identified contributors to intramuscular and intratendinous HO is the presence of PDGFRα+ cells (presumptive FAPs) within the heterogeneous composition of labeled cells[38,65,94,122,123]. In addition, in the burn/tendonectomy model, large aggregates of highly proliferative PDGFRα+ mesenchymal-like cells accumulated at the injury site immediately prior to the onset of HO[122,123].…”
Section: Progenitors Of Heterotopic Ossificationmentioning
confidence: 99%
“…In fact, one underlying commonality among most lineage-tracing studies that have identified contributors to intramuscular and intratendinous HO is the presence of PDGFRα+ cells (presumptive FAPs) within the heterogeneous composition of labeled cells[38,65,94,122,123]. In addition, in the burn/tendonectomy model, large aggregates of highly proliferative PDGFRα+ mesenchymal-like cells accumulated at the injury site immediately prior to the onset of HO[122,123]. These PDGFRα+ cells were positive for the cartilage marker SOX9, and reappeared during recurrent HO resulting from partial surgical excision of the initial HO[123].…”
Section: Progenitors Of Heterotopic Ossificationmentioning
confidence: 99%
See 1 more Smart Citation
“…However, options for prevention include non-steroidal anti-inflammatory drugs (NSAIDs) which reduce inflammation and have been used with patients after orthopedic procedures [3036], radiation therapy which is directed to specific sites where HO may predictably form [10, 3646], and bisphosphonates [47]. In burn patients, these preventative strategies may have more value for secondary prevention after initial excision – patients who have already undergone HO resection are at high risk for developing a second lesion or recurrence at the site of excision [48] and may be amenable to directed therapy.…”
Section: Preventionmentioning
confidence: 99%